Efektivitas Jus Kacang Kedelai Terhadap Kadar Hemoglobin Remaja Puteri - Olii, Nancy; Salman, Salman; Ischak , Wenny Ino; Manueke, Iyam; Donsu , Amelia; Nurdin, Siti Surya Indah; Abdul, Nurnaningsih Ali (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The highest percentage of anemia occurs among adolescent girls, and one of the efforts to overcome such problem is iron supplementation along with iron-rich foods from animal sources such as red meat and marine products, as well as vegetable sources such as nuts. Soybean is a kind of iron-rich food which contains 8.0/100 g of iron. This study aims to observe the increase in hemoglobin levels after the administration of soybean juice among adolescent girls. This was a pre-experimental study with a one group pretest-posttest design. The populations consisted of 133 adolescent girls of VII and VIII graders with a sample size of 35 respondents who were selected by using purposive sampling technique. The respondents were given 250 ml of soybean juice for 21 consecutive days every morning. On the twenty-second day, the Hb levels of respondents were re-assessed (post-test). The blood sample taken was a capillary blood at the fingertip. The statistical test applied the Paired T-Test. The results revealed that hemoglobin levels of respondents who were given soybean juice increased by 12.06 g/dl with a difference of 1.62 g/dl. This study concluded that 250 ml soybean juice had an effect on the hemoglobin levels among adolescent girls. Adolescents are recommended to regularly consume iron-rich foods and beverages with various kinds of preparations such as soybean juice.